SNOW TRANSPORT EQUIPMENT - PETER JUNIOR SNOW MILLER TESTS - Hansen, Robert W. (1963)
During the summer season of Deep Freeze 62 tests were made with a Peter Junior Snow Miller to determine its suitability for clearing drift in a surface camp on snow and to determine the fea sibility of transporting construction snow with a snow plow. These tests were made on the Ross Ice Shelf near McMurdo Station in air temperatures ranging between 20 F and 30 F. Mechanical performance of the snow plow was satisfactory at these temperatures and it could be worked in close to a building with ease and safety. How ever, it was concluded that the plow was not practical for clearing drift in camps on snow unless the surface in the camp area was hard and firm. A test on the transport of snow for con structing elevated snow-compacted roads and run ways showed that a snow plow appeared feasible for this work. It was concluded that the in vestigation on the transport of construction snow with a snow plow should be continued using a tractor-mounted plow as the test vehicle. (Author)